An Integrated Platform for Serological Detection and Vaccination of COVID-19 - Wei, Sung-Chan; Hsu, Wei-Ting; Chiu, Chun-Hsiang; Chang, Feng-Yee; Lo, Huei-Ru; Liao, Chuan-Yu; Yang, Hwai-I; Chou, Yu-Chi; Tsai, Chih-Hsuan; Chao, Yu-Chan (Frontiers in Immunology, 2021)
Coronavirus Disease 2019 (COVID-19), caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), is an ongoing pandemic. Detection and vaccination are essential for disease control, but they are distinct and complex operations that require significant improvements. Here, we developed an integrated detection and vaccination system to greatly simplify these efforts. We constructed recombinant baculoviruses to separately display the nucleocapsid (N) and spike (S) proteins of SARS-CoV-2. Insect cells infected by the recombinant baculoviruses were used to generate a cell-based system to accurately detect patient serum. Notably, although well-recognized by our newly developed detection system in which S-displaying insect cells acted as antigen, anti-S antibodies from many patients were barely detectable by Western blot, evidencing that COVID-19 patients primarily produce conformation-dependent anti-S antibodies. Furthermore, the same baculovirus constructs can display N (N-Bac) or S (S-Bac) on the baculovirus envelope and serve as vector vaccines. Animal experiments show that S-Bac or N-Bac immunization in mice elicited a strong and specific antibody response, and S-Bac in particular stimulated effective neutralizing antibodies without the need for adjuvant. Our integrated system maintains antigen conformation and membrane structure to facilitate serum detection and antibody stimulation. Thus, compared with currently available technologies, our system represents a simplified and efficient platform for better SARS-CoV-2 detection and vaccination.